2004
DOI: 10.1088/0022-3727/37/9/r01
|View full text |Cite
|
Sign up to set email alerts
|

Vertical-external-cavity semiconductor lasers

Abstract: Surface-emitting semiconductor lasers can make use of external cavities and optical pumping techniques to achieve a combination of high continuous-wave output power and near-diffraction-limited beam quality that is not matched by any other type of semiconductor source. The ready access to the laser mode that the external cavity provides has been exploited for applications such as intra-cavity frequency doubling and passive mode-locking. The purpose of this Topical Review is to outline the operating principles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(74 citation statements)
references
References 50 publications
0
74
0
Order By: Relevance
“…Because of uncompensated higherorder chirp, only 6 nm sweep range has been used, which currently is the reason for limited pulse energies of B140 pJ (without EDFA) and B5.6 nJ (with EDFA). Concerning the achievable pulse energy, these results cannot compete with master oscillator fibre power amplifier systems 39 , but are comparable to semiconductor-based, optically pumped VECSELs 15,16 or semiconductor-based master oscillator power amplifier systems 12,14 . Nevertheless, it should be emphasized that in spite of current experimental restrictions, already the B140 pJ is higher than typical pulse energies achievable with conventionally mode-locked SOA-based semiconductor lasers 9 , even in the case of using an eXtreme chirped pulse oscillator approach 40 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Because of uncompensated higherorder chirp, only 6 nm sweep range has been used, which currently is the reason for limited pulse energies of B140 pJ (without EDFA) and B5.6 nJ (with EDFA). Concerning the achievable pulse energy, these results cannot compete with master oscillator fibre power amplifier systems 39 , but are comparable to semiconductor-based, optically pumped VECSELs 15,16 or semiconductor-based master oscillator power amplifier systems 12,14 . Nevertheless, it should be emphasized that in spite of current experimental restrictions, already the B140 pJ is higher than typical pulse energies achievable with conventionally mode-locked SOA-based semiconductor lasers 9 , even in the case of using an eXtreme chirped pulse oscillator approach 40 .…”
Section: Discussionmentioning
confidence: 88%
“…Increased pulse energies can be achieved using the semiconductor-based eXtreme chirped pulse amplification concept 9 , where pulses are stretched temporally before amplification and the output energy of the recompressed pulse then exceeds the fundamental energy-storage limit of the semiconductor gain medium. Besides edge-emitting diodes, ultrashort pulses can be generated with optically pumped, passively mode-locked VECSELs 15 exhibiting increased saturation power and, thus, allowing for comparably high average output powers and pulse energies 16 . However, disadvantages of optical pumping can be, especially at high average power, a lower wall-plug efficiency and the need for a more sophisticated thermal management.…”
mentioning
confidence: 99%
“…9), which also reduces the cavity losses by decreasing the field strength in the doped top layer. However, the sub-cavity between the two DBRs has a strong spectral filtering effect [3], which reduces the bandwidth of the device. Hence, the minimum achievable pulse width by mode locking is increased.…”
Section: 4mentioning
confidence: 99%
“…It will be shown that a trade off between the conflicting optical and electrical optimization has to be found and we derive an optimized design resulting in guidelines for the design of EP-VECSELs which are compatible with passive mode locking. Vertical-external-cavity surface-emitting lasers (VECSELs) [1] are of high scientific and industrial interest due to their large fundamental transverse mode output power, scaling with the device radius, the near diffraction limited output beam, and the suitability for intracavity frequency conversion [2] and passive mode locking [3,4]. Passive mode locking of an optically pumped VECSEL has been demonstrated with a semiconductor saturable absorber mirror (SESAM) [5] in a folded external cavity.…”
mentioning
confidence: 99%
“…They also became attractive to the diodepumped solid-state laser community as they constitute a variation on the doped-dielectric thin-disk concept [8,9], with the advantage of a bandgap engineered emission wavelength and a simplified pumping scheme. Since then, this combined interest and application-driven developments have made this technology the subject of vibrant topical research [10][11][12][13]. In this review, after an overview of potential applications, we provide a tutorial on the design and engineering of visible and ultraviolet (UV) emitting SDLs as well as an up-to-date summary of their performance.…”
Section: Introductionmentioning
confidence: 99%